UJI EFIKASI AGENS HAYATI TERHADAP PENYAKIT HAWAR DAUN BAKTERI (Xanthomonas oryzae pv. oryzae) PADA BEBERAPA VARIETAS PADI SAWAH (Oryza sativa) - Syahrial Damanik; Mukhtar Iskandar Pinem; Yuswani Pengestiningsih (Jurnal Agroekoteknologi, 2013)
Syahrial Damanik, Biological agents efficacy test to blight leaf disease Xanthomonas oryzae pv.oryzae on some rice varieties (Oryza sativa). The aim of this research was to find suitablebiological agens to inhibit attack from blight leaf disease and also to discover most resistentvarieties to wants Leaf Blight Disease.This research was conducted using randomized completelydesign (RCD) factorial consisting of two treatment factors and three replications. The first factornamely T0, T1, T2 (Control, Pseudomonas fluorescens, Trichoderma sp with Pseudomonasfluorescens) the second factor’s variety V1, V2, V3 (Inpari 13, Mekongga, Ciherang).The result showed that on Biological agents treatment, the lowest disease intensity occured atTrichoderma sp with Pseudomonas fluorescens of 4.74 % and highest intensity disease occured atControl for 23.14 %. Varieties treatment had the lowest disease intensity in Ciherang for 7.79 %and highest disease intensity in Inpari 13 for 19.06 %. Interaction between biological agents andvarieties had the lowest disease intensity in Trichoderma sp with P. fluorescens and Inpari 13 for3.77 % and highest in Control and Mekongga for 33.97 %. The highest production in biologicalagents treatment occured in Trichoderma sp with P. fluorescens for 7.46 tons/ha and the lowest inControl for 3.63 tons/ha. The highest production on varieties treatment occured in Ciherang for 6.40tons/ha and the lowest in Inpari 13 for 4.98 tons/ha.Keywords : biological agents, varieties, Xanthomonas oryzae pv. oryzae, rice.